2022
DOI: 10.1002/btm2.10432
|View full text |Cite
|
Sign up to set email alerts
|

Tracking motion kinematics and tremor with intrinsic oscillatory property of instrumental mechanics

Abstract: Tracking kinematic details of motor behaviors is a foundation to study the neuronal mechanism and biology of motor control. However, most of the physiological motor behaviors and movement disorders, such as gait, balance, tremor, dystonia, and myoclonus, are highly dependent on the overall momentum of the whole-body movements. Therefore, tracking the targeted movement and overall momentum simultaneously is critical for motor control research, but it remains an unmet need.Here, we introduce the intrinsic oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 64 publications
(156 reference statements)
0
3
0
Order By: Relevance
“…Based on this initial observation, we trained the mice with a protocol including multiple vibratory frequencies (Fig. 1g), covering the physiological frequency range of spontaneous motor behaviors 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this initial observation, we trained the mice with a protocol including multiple vibratory frequencies (Fig. 1g), covering the physiological frequency range of spontaneous motor behaviors 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Cerebellar dysfunctions lead to the breakdown of motor kinematic control in a unique feature linked to motor frequencies. Essential tremor, the most common movement disorder, is characterized by involuntary rhythmic movements with a consistent motor 5 frequency, linked to excessive cerebellar oscillations [13][14][15] . Conversely, cerebellar ataxia features arrhythmic involuntary movements, that are associated with Purkinje cell loss 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that tremor frequencies and amplitudes are regulated by different mechanisms. The intensity of cerebellar oscillations in both mice and humans has been linked to tremor amplitudes ( 20 , 22 , 41 ), potentially reflecting the synchrony of PC complex spikes and DCN neurons ( 33 , 35 , 48 51 ). Amplitude-based analysis also revealed that cerebellar tACS at the tremor frequency can bidirectionally modulate tremor amplitudes in patients with ET ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Grid2 dupE3 mice were used as a mouse model of ET with pathological and electrophysiological characteristics similar to the human disease ( 20 ). Electrophysiology was incorporated with force plate–based motion tracking ( 41 ) in freely moving mice. Viral-based optogenetic tools and transgenic mice were applied to validate tremor-generating mechanisms in nontremulous mice or modulate tremor frequencies in Grid2 dupE3 mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation